A new potential of sodium anthraquinone-2-sulfonate as a corrosion inhibitor for carbon steel in 0.5 M H2SO4 - Nikolay Akatyev; Roza Kenzhegalieva; Meruyet Khapiyeva; Gauhar Uzakbay; Aruzhan Talapova; Ruben Vardanyan (Journal of Electrochemical Science and Engineering)
The present study investigates the inhibitory properties of sodium anthraquinone-2-sulfonate (AQ2SNa). Weight loss measurements, electrochemical tests, and metal surface analysis were carried out in this study to evaluate the adsorption behavior of the compound and its influence on the corrosion rate of carbon steel in 0.5 mol dm-3 H2SO4 solution. Density functional theory DFT/B3LYP/6-311+G(d,p) and molecular dynamic simulation (MD) were applied for theoretical studies to evaluate the inhibiting effect and understand the mechanism of interaction of inhibitor molecules with Fe (110) surface. It was found that the inhibition efficiency of AQ2SNa in 0.5 mol dm-3 H2SO4 solution reached up to 94.44 % at the maximum concentration (0.5 g dm-3). Thermodynamic parameters show that the adsorption process is spontaneous and endothermic, suggesting the conformance of strong interactions between inhibitor and metal surface according to the Langmuir adsorption model. The spontaneous physisorption (ΔG0ads ˃ -20 kJ mol-1) of the inhibitor molecules led to high efficiency. Analysis of dynamic polarization curves showed that AQ2SNa acts as an inhibitor of a mixed nature. The results also indicate that AQ2SNa significantly increases the contact angle, indicating increased hydrophobicity due to the formation of a stable film on the metal surface. Theoretical parameters were compared to experimental data. The results highlight the novel potential of AQ2SNa as an effective corrosion inhibitor to provide an effective solution for enhancing the protection of carbon steel in acidic media.